Stress distribution in ceramic restorations over natural tooth using sing finite element analysis. lithium disilicate x aluminum oxide material - Júnior, Amilcar Chagas Freitas [UNESP] (2013)
Background: Data on stress distribution in tooth-restoration interface with different ceramic restorative materials are limited. The aim of this chapter was to assess the stress distribution in the interface of ceramic restorations with laminate veneer or full-coverage crown with two different materials (lithium dissilicate and densely sintered aluminum oxide) under different loading areas through finite element analysis. Materials and Methods: Six two-dimensional finite element models were fabricated with different restorations on natural tooth: laminate veneer (IPS Empress, IPS Empress Esthetic and Procera AllCeram) or full-coverage crown (IPS e.max Press and Procera AllCeram). Two different loading areas (L) (50N) were also determined: palatal surface at 45° in relation to the long axis of tooth (L1) and perpendicular to the incisal edge (L2). A model with higid natural tooth was used as control. von Mises equivalent stress (δvM) and maximum principal stress (δmax) were obtained on Ansys software. Results: The presence of ceramic restoration increased δvM and δmax in the adhesive interface, mainly for the aluminum oxide (Procera AllCeram system) restorations. The full-coverage crowns generated higher stress in the adhesive interface under L1 while the same result was observed for the laminate veneers under L2. Conclusions: Lithium dissilicate and densely sintered aluminum oxide restorations exhibit different behavior due to different mechanical properties and loading conditions.